Postmodern Quranic Interpretation in Pop Culture: An Antithesis to The Authority of Traditional Interpretation - Romario; Pohan, Zulfikar Riza Hariz (Kodifikasia, 2025)
This article examines the interpretation of the Al-Quran in the discourse of pop-culture in the era of postmodernism which emerged in Instagram account @quranreview. This research method uses a netnographic approach in looking at the patterns and posts from the @quranreview account. The results of this study indicate that in the old religious authorities, Al-Quran interpretation could only be carried out by a commentator with in-depth knowledge, but after the development of technology the interpretation of the Al-Quran was no longer the authority of the interpreter, but has shifted to a new religious authority which packs Al-Quran interpretations. Quran with light packaging and can be understood by ordinary people. @quranreview uses modern language and the tastes of young people in its posts to attract the interest of Instagram users and invites them to interpret verses freely through published books.